Enteric coronavirus infection in adult horses. (January 2018) - Pusterla, N.; Vin, R.; Leutenegger, C.M.; Mittel, L.D.; Divers, T.J.
Highlights: Equine coronavirus (ECoV) is a newly recognized enteric virus of adult horses. Infection with ECoV has been associated with fever, lethargy and anorexia, as well as colic and diarrhea. Outbreaks of ECoV infection have been reported in Japan, Europe and the USA since 2010. Abstract: A new enteric virus of adult horses, equine coronavirus (ECoV), has recently been recognized. It is associated with fever, lethargy, anorexia, and less frequently, colic and diarrhea. This enteric virus is transmitted via the feco-oral route and horses become infected by ingesting fecally contaminated feed and water. Various outbreaks have been reported since 2010 from Japan, Europe and the USA. While the clinical signs are fairly non-specific, lymphopenia and neutropenia are often seen. Specific diagnosis is made by the detection of ECoV in feces by either quantitative real-time PCR, electron microscopy or antigen-capture ELISA. Supportive treatment is usually required, as most infections are self-limiting. However, rare complications, such as endotoxemia, septicemia and hyperammonemia-associated encephalopathy, have been reported, and have been related to the loss of barrier function at the intestinal mucosa. This review article will focus on the latest information pertaining to the virus, epidemiology, clinical signs, diagnosis, pathology, treatment and prevention of ECoV infection in adult horses.